The effect of cognitive rehearsal training on performance and self-report of anxiety in novice and intermediate female gymnasts - Decaria, M. D. (1977)
Cognitive rehearsal (CR) was defined as consisting of two elements: (a) progressive relaxation training, and (b) mental practice of the intended task. Ss were evaluated according to a multiple-baseline experimental design with CR as the independent variable. It was found that: 1. CR moderately enhanced performance in the intermediate standard Ss. 2. CR produced an immediate, but not cumulative, decrease in the self-report of performance anxiety for intermediate performers. 3. CR produced a significant cumulative, but not immediate, decrease in the self-report of performance anxiety in novice standard gymnasts. Implication: Relaxation training and mental imagery of intended gymnastics tasks contributes to good or improved performances and makes the competitive setting more enjoyable by reducing competitive anxiety in novice and intermediate standard gymnasts.